Impacts of MicrofinanceInstitutions: Issues and Concepts-An Empirical Study on Sri Lankan Context - Rathiranee, Y. (International Journal of Socio-Economic and Environmental Outlook, 2014)
Micro Finance Institutions (MFIs) Provide financial and non financial services to the poor people in developing countries for their income generating activities as well as in Sri Lanka. It can be divided into different legal categories depending on the country in which the institution is based. An MFI could be aNon Government Organization (NGO), a credit cooperative or a non-bank financial institution and Community Based Organizations (CBOs). It has dual objectives which are both social and financial. The social objectives mean that the MFI contributes to improvement and alleviating poverty. The financial objectives focus that the MFI must keep enough profit for their sustainability. MFIs provide financial, social intermediation, entrepreneurship development and social services to the clients for achieving the social objectives. Microfinance in Sri Lanka has a long history and MFIs are established in all forms and dimensions and it can differ in size, practice, legal act, strategy and budget. The reliability is important to the microfinance system and it determines how smoothly an MFI operates. The aim of this study is to examine the impacts of MFIs in Sri Lanka at household level and community level. This concept paper focuses on a review of academic literature on impacts of various activities when it provides services to the clients. The research designs both combining quantitative and qualitative tools are used. For this purpose, previous studies from developed and developing countries on this regards have been examined and then found out the solutions from the literatures that were the secondary data on which have been derived from reports, documents and research papers of NGOs, government departments and MFIs etc., In addition to this, the primary data was gathered through the direct personal interviews (questionnaires) from the clients of MFIs such as Samurthi, Women rural development societies(WRDS) and Thrift Cooperative Credit Societies (TCCSs)who are living in the rural areas of Valikamam North and East Divisional Secretariat (DS) Divisions and Thenmaradchi DS Divisions have been selected. With the history of MF in Sri Lanka, the concepts such as Governance, clients, operations and products have been explained and challenges or issues facing MFIs were taken into account for the investigation of the MFIs in Sri Lanka. Finally it was concluded from the comprehensive literatures and observed primary data gathered from the study area, that the impact of MF is significant at household and community level. Further, the women empowerment is significant impact on MF since most of the clients of MFIs are women. However, micro credit has negative impacts on people’s feeling because most people are more concerned about paying back the loan and they expect the marketing and financial difficulties with the increasing cost of living in Sri Lanka.
Keywords: MFIs; Impact; Concept; Issues